Distribution of Blood Groups in Medical Students: A Comparative Study - Joshi, Bishal; Kar, Sanjit Kumar; Yadav, Shankar; Yadav, Prem Kumar; Mahotra, Narayan Bahadur; Shrestha, Laxmi; Shrivastava, Amit Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Blood groups depend on antigens present on the surface of red blood cells. Scientists have discovered at least 30 common antigens and hundreds of rare antigens causing antigen-antibody reaction in human red blood cells. These antigens are genetically determined and are developed in fetal life and remain unchanged till death. Many blood group systems are identified but ABO and Rh blood groups are more antigenic. MATERIAL AND METHODS: In the present study, we observed ABO and Rh blood groups of 3057 students who studied in Universal College of Medical Sciences, Bhairahawa, Nepal from 1998 AD to 2019 AD, using open slide test method. The data was analyzed using SPSS version 20. RESULTS: Results of the present study indicated that the most common blood group was O (36.8%) followed by blood group B (31.1%) and blood group A (24.9%) and least common blood group was AB (7.2%) i.e. O>B>A>AB. The same sequence of ABO blood grouping was seen in both male and female. Rh positive blood group was found in 95.4% and Rh negative blood group was found in 4.6% of population. CONCLUSION: Knowledge of distribution of blood group is very important for medical students as they can serve as immediate blood donor in emergency conditions. This study can provide insight to advanced studies in future which can relate blood groups with medical conditions.